Performance Measurement Using Balanced Scorecard in Prime Plaza Hotel Sanur-Bali - M T P Chrisanti; I M M Arsana; L M Wahyuni (Journal of Applied Sciences in Accounting, Finance, and Tax, 2018)
Performance measurement of Prime Plaza Hotel Sanur-Bali focuses on financial and customer aspects. That measurements are not enough to describe the entirety performance of the company. The entirety performance can be measured by balanced scorecard concept. The purpose of this research is to determine the performance of Prime Plaza Hotel Sanur-Bali using Balanced Scorecard concept based on financial perspective, customer perspective, internal business process perspective, and learning and growth perspective. Data collections were through observation, interview, documentation, and questionnaires. The result showed that the performance of financial perspective is good, measured by the ratio of liquidity, solvability, activity, and profitability. Customer’s perspective shows the customer is satisfied with the services and facilities. The perspective of internal business process shows there is some innovations and after-sales service, the efficiency of service time check in and check out still need improvement. The learning and growth perspective shows the employees are satisfied with their work, and low employee retention rates. In general, the performance of Prime Plaza Hotel Sanur-Bali is good. However, it still needs improving the efficiency of service time, human resource management orientation that concerns welfare, optimization of asset management.